If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(b + -12) = 0 Reorder the terms: 6(-12 + b) = 0 (-12 * 6 + b * 6) = 0 (-72 + 6b) = 0 Solving -72 + 6b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '72' to each side of the equation. -72 + 72 + 6b = 0 + 72 Combine like terms: -72 + 72 = 0 0 + 6b = 0 + 72 6b = 0 + 72 Combine like terms: 0 + 72 = 72 6b = 72 Divide each side by '6'. b = 12 Simplifying b = 12
| 48/40=x/40 | | 4a+3whena=2 | | z=90-4x+6y | | 4x^2=61x+119 | | -(7-t)=21 | | z^2-64= | | x=(180-2x+3y)-(90-2x+3y) | | x=(180-2x+3y)-(190-2x+3y) | | 6(z-3)=30 | | -1.5+0.5y^2=y | | 3(y^2-2x-3)=0 | | 3(m+5)=27 | | (3y^2)-6x-9=0 | | 24+14y+y= | | -11/-5 | | 7x+3y=3.58 | | 5(f+2)=20 | | 2+(-6)+3= | | (y^2)dy+(2xy^3-6x)dx=0 | | 7(b-1)=14 | | 37x-28-37x=37x-28-37x | | 5log(4x+1)=7 | | 6-(7)+3= | | 2.9+5=4.7w-7.6 | | (-2xy^2)*(3x^3y)= | | 2(5x-4)=2(19x+12) | | 90=(2-w)(5+w) | | 6xy^2*4xy= | | x^3=360 | | y^2-6xy+5x^2=0 | | f(x+h)=x^2-8x | | 0.99+27=42.72 |